PHY150: Electricity and Magnetism - UiTM, Faculty of Applied Sciences (2023)
In Electricity and Magnetism, topics include Electric Charge, Electric Field, Electric Potential, Capacitance, Electric Current, DC Circuits, Magnetism, Inductance and Alternating Current.